Antibiotic prophylaxis in ragged placental membranes: a prospective, multicentre, randomized trial - Hian Yan Voon; Jun Yan Pow; Lee Na Tan; Haris Njoo Suharjono; Wan Sim Teo (BMC, 2019)
Abstract Background Ragged placental membranes is a distinct entity from retained placenta and not uncommonly reported in midwifery texts. Although the incidence of postpartum endometritis is merely 1-5% after vaginal births, it remains the most common source of puerperal sepsis, contributing up to 15% of maternal mortality in low income countries. Geographically-remote centres in Malaysia prophylactically administer antibiotics for women with ragged placental membranes after vaginal birth, extrapolating evidence from retained placenta. We sought to clarify the rationale in continuing such practices. Methods This was an open-label, prospective, multicentre, randomized trial. Three hospitals where the current protocol was to administer prophylactic amoxycillin-clavulanic acid served as the sites of recruitment. Women who delivered vaginally beyond 24+ 0 weeks of gestation with ragged membranes were invited to participate in the trial and randomized into prophylaxis or expectant management with medical advice by blocks of 10, at a 1:1 ratio. A medication adherence diary was provided and patients followed up at 2 weeks and 6 weeks postpartum. Results A total of 6569 women gave birth vaginally in three centres during the trial period, of which 10.9% had ragged membranes. The incidence of endometritis was not significantly raised in women with or without prophylaxis (0.90% vs 0.29%; p = 0.60). All cases of endometritis presented within the first 2 weeks and preventive use of antibiotics did not ameliorate the severity of endometritis since rates of ICU admission, surgical evacuation and transfusion were comparable. Conclusion Preventive use of antibiotics after vaginal delivery in women with ragged placental membranes did not result in a reduction of endometritis. Educating women on the signs and symptoms of endometritis would suffice. Based on the reported incidence of ragged membranes, a change in practice would result in 1500 less prescriptions of antibiotics per annum in these three centres. Trial registration NCT 03459599 (Retrospectively registered on 9 March 2018).